Continuation of gefitinib plus chemotherapy prolongs progression-free survival in advanced non-small cell lung cancer patients who get acquired resistance to gefitinib without T790M mutations - Ding, Ting (J Thorac Dis, 2017)
BACKGROUND: Aimed to identify the benefit population from continuation of epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs), this study investigated the efficacy of continuation of EGFR-TKIs plus chemotherapy beyond the response evaluation criteria in solid tumors-progressive disease (RECIST-PD) according to different progression modes and T790M mutational status. METHODS: From November 2009 to July 2015, 630 patients with advanced non-small cell lung cancer (NSCLC) receiving gefitinib as initial EGFR-TKI treatment were screened in Shanghai Pulmonary Hospital. A total of 170 patients with documented gradual or dramatic progression after gefitinib treatment who received chemotherapy alone or in combination with gefitinib were included. Post-RECIST-PD progression-free survival (PPFS) between continuation of gefitinib plus chemotherapy and chemotherapy alone was assessed. RESULTS: The incidence of T790M mutation was 42.9% (63/147) in patients who got acquired resistance in this study. Median PPFS was 4.0 months [95% confidence interval (CI), 3.1–4.9 months] in the chemotherapy group and 5.0 months (95% CI, 3.6–6.4 months) in the combination group with a borderline statistical significance (P=0.071). Continuation of gefitinib plus chemotherapy resulted in a significant improvement in PPFS compared with chemotherapy alone in patients with EGFR(T790M)-negative tumors [median PPFS: 6.6 vs. 3.5 months, hazard ratio (HR) 0.50, 95% CI, 0.29–0.88; P=0.011], especially in pemetrexed-based chemotherapy (HR 0.45, 95% CI, 0.24–0.86; P=0.011). PPFS was similar in patients with EGFR(T790M)-positive tumors (median PPFS: 5.0 vs. 5.5 months, HR 0.80, 95% CI, 0.40–1.61; P=0.520) or EGFR(T790M)-unknown tumors (median PPFS: 2.0 vs. 3.0 months, HR 1.40, 95% CI, 0.69–2.81; P=0.323). CONCLUSIONS: Our study showed that continuous gefitinib plus chemotherapy, especially pemetrexed-based therapy, significantly improved PPFS in patients with EGFR(T790M)-negative tumors as compared with chemotherapy alone, suggesting that this subtype of patients may derive clinical benefit from continuation of gefitinib treatment beyond progression.